Study on the process of Determination of Cadmium and Lead in Some Vegetables in Lam Thao - PhuTho by F-AAS Method - Pham, Xuan Du; Nguyen, Tien Khi; Tran, Thi Thuy; Vu, Anh Tuan (Old Journal, 2019)
In this paper, we studied the process of analysis cadmium and lead in green vegetable samples by flame atomic absorption spectrometry (F-AAS). The conditions of analysis such as acid concentration, subtracted solution, releasing reagent have been investigated and optimized. Effect of foreign ions on spectral line intensity was also investigated. At the optimized conditions (HNO₃ concentration of 1%, CH₃COONH₄ concentration of 1%, LaCl₃ concentration of 1%), the analysis procedure showed the high accuracy and repeatability. The linear ranges of Cd and Pb were 0.014 ppm and 0.05-8 ppm, respectively. The limit of detection (LOD) and (LOQ) of Cd were 0.0092 and 0.0310 ppm, respectively and these values for Pb were 0.0090 and 0.0300 ppm. In addition, the procedure was applied to analyze the 10 green vegetable samples grown in Lam Thao district, Phu Tho province.